ANALYSIS OF THE CURRENT STATE OF THE HOTEL INDUSTRY IN BLACKPINK (Marketing Journal, 2025)
This study aims to systematically analyze the current state of the hotel industry in the Republic of Karakalpakstan. Data were collected based on official statistics. The research examines inbound and domestic tourism, types of hotel services, infrastructure quality, service standards, and key economic indicators. Regional specificities, seasonality, and marketing potential were also assessed. Based on the findings, major challenges in the sector were identified, and practical recommendations for improvement were proposed.
Keywords: Karakalpakstan; hotel industry; tourism infrastructure; service quality; economic indicators; seasonality; marketing potential. 189